2011
DOI: 10.1186/1756-3305-4-26
|View full text |Cite
|
Sign up to set email alerts
|

Are protozoan metacaspases potential parasite killers?

Abstract: Mechanisms concerning life or death decisions in protozoan parasites are still imperfectly understood. Comparison with higher eukaryotes has led to the hypothesis that caspase-like enzymes could be involved in death pathways. This hypothesis was reinforced by the description of caspase-related sequences in the genome of several parasites, including Plasmodium, Trypanosoma and Leishmania. Although several teams are working to decipher the exact role of metacaspases in protozoan parasites, partial, conflicting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 46 publications
0
36
0
2
Order By: Relevance
“…Meslin et al (55) reported the involvement of terpenoids in the activation of programmed cell death in Plasmodium species, and in the interference of one or more substances in the process of cell differentiation of the parasite, which has proven to be an extremely complex process, with fine-tuned regulation of gene expression, resulting in a turnover of proteins and destruction of organelles present in Plasmodium, as well as other species of pathogenic protists (56) .…”
Section: Discussionmentioning
confidence: 99%
“…Meslin et al (55) reported the involvement of terpenoids in the activation of programmed cell death in Plasmodium species, and in the interference of one or more substances in the process of cell differentiation of the parasite, which has proven to be an extremely complex process, with fine-tuned regulation of gene expression, resulting in a turnover of proteins and destruction of organelles present in Plasmodium, as well as other species of pathogenic protists (56) .…”
Section: Discussionmentioning
confidence: 99%
“…T. brucei expresses five isoforms (TbMCA 1–5) of this enzyme, with isoforms 2, 3 and 5 being validated as drug targets . While the precise role that metacaspases play in protozoa is yet to be fully understood, they have been implicated in programmed cell death . Owing to their apparent necessity in trypanosomes coupled to their absence in mammals, Berg et al.…”
Section: Kinetoplastids (Trypanosomiasis and Leishmaniasis)mentioning
confidence: 99%
“…Caspase-like activity is usually detected by studies using substrate-inhibition assays, however, these assays may not be absolutely specific for the clan CD cysteine proteases that the caspases belong to (discussed in [47]), and the involvement of metacaspases in apoptosis in P. falciparum has been contested [80] - although see [42,81]. Other proteases have now been identified as being involved in the apoptosis pathways of parasitic protists.…”
Section: Reviewmentioning
confidence: 99%